Limb Salvage for Primary Malignant Bone Tumors of the Distal Leg in Skeletally Immature Patients: Ankle Arthrodesis Using Vascularized Ipsilateral or Contralateral Fibular Flap - El Ghoneimy, Ahmed Mohamed; Sokar, Mohamed; Kamal, Nehal (Journal of Reconstructive Microsurgery Open, 2019)
Background Malignant bone tumors of the distal tibia or fibula in children are rare. Quality of functional outcome following limb salvage surgery is still controversial. This is a retrospective review of the functional outcome of ankle arthrodesis using vascularized fibular flap.Methods A total of seven patients were reviewed. The diagnosis was osteosarcoma in five and Ewing's sarcoma in two patients. The primary tumor site was the distal tibia in six patients and the distal fibula in one patient. The average age at presentation was 10.6 years (range, 6.7–14 years). The average follow-up period was 24.5 months (range, 13–69 years). A pedicled fibular graft was harvested from the ipsilateral leg in two patients and a free vascularized osteocutaneous fibular flap from the contralateral leg in five patients. External fixation was used in five and internal fixation in two patients. Patients were allowed full weight bearing following radiographic evidence of complete bone union.Results The mean time to complete bone union and full weight bearing was 7.1 months (range, 4–13 months). One patient developed nonunion at graft-host junction and one patient had stress fracture of the fibular graft. The mean limb length inequality was 0.57 cm (range, 0–3 cm). The average Musculoskeletal Tumor Society (MSTS) score was 84.5% (range, 73–100%).Conclusion Skeletally immature patients treated by ankle arthrodesis using vascularized fibular flap can return to full weight bearing within the first year following surgery. A contralateral fibular flap has the advantage of preserving the contour of the ankle and reserving the ipsilateral fibula for initial stability at the fusion site. This study is of level IV evidence.
Keywords: osteosarcoma; Ewing's sarcoma; distal tibia; vascularized fibular graft; ankle arthrodesis